DETEKSI NEUROPATI PERIFER MENGGUNAKAN VIBRASI PADA PASIEN DIABETES MELITUS: TINJAUAN LITERATUR - Jasmin, Muh; Romantika, I Wayan; Sakinah, Sri (Jurnal Kesehatan Marendeng, 2025)
The American Diabetes Association's "Standards of Medical Care in Diabetes" that for Diabetic Peripheral Neuropathy (DPN) screening can use 10 gram Semmes Weinstein Monofilament (SWM) tests, temperature, puncture sensations. This study aims to evaluate vibration sensations in detecting peripheral neuropathy in patients DM. The design of this study was a literature review and was prepared based on the 2009 PRISMA guidelines checklist. Literature search was carried out with the keyword "diabetes mellitus AND vibration AND peripheral neuropathy". The databases used are PubMed, ScienceDirect, ProQuest, Google Scholar, and DOAJ which have been reported in English for the past eight years. There were 9 articles included in this study using cross sectional design, quasi experiment, and cohort study. 3 studies evaluated VibraTip, each 1 article evaluating Mobile Vibration, Neuropad, NerveChek, VSA-3000, and 1 article comparing ESC with VPT. From the results of the assessment in the inclusion article it was found that vibration can be significantly used to detect peripheral neuropathy in patients DM. The findings from this review indicate that vibration is very useful for detecting peripheral neuropathy.